Shoppers Stop: Leveraging Social Media for Employer Branding. Issue 1 (June 2020) - Saini, Gordhan K.
Shoppers Stop had a significant presence on social media platforms—LinkedIn, Facebook, Twitter and YouTube. However, a large number of Shoppers Stop's customers posted complaints about deficiency in customer service on these social media platforms, mainly on Facebook. The complaints and ratings were also seen by other stakeholders such as potential employees who form a perception about the company's employer brand based on these ratings. While Shoppers Stop promptly responded to disgruntled customers on Facebook to redress their complaints, Shoppers Stop was uncertain about the possible adverse impact of these customer reviews on the company's employer brand. Further, Shoppers Stop wanted to leverage its presence on various social media platforms to promote and manage its employer brand.